2020
DOI: 10.1186/s13046-020-01657-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: IMP3 accelerates the progression of prostate cancer through inhibiting PTEN expression in a SMURF1-dependent way

Abstract: Background Insulin-like growth factor 2 (IGF2) messenger RNA binding protein 3 (IMP3) has been testified to be overexpressed in prostate cancer and strongly related to patients’ poor prognosis. However, the functions of IMP3 and the underlying mechanisms in prostate cancer still remain unknown. Therefore, the current study was carried out to reveal the role and molecular mechanism of IMP3 in prostate cancer progression. Methods The expression levels of IMP3 in prostate cancer tissues and cells were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
4
27
0
Order By: Relevance
“…There are also some reports in PC. Furthermore, the role of IGF2 messenger RNA binding protein 3 (IMP3) produces an acceleration in PC progression through activating PI3K/AKT/mTOR signaling pathway via increasing SMURF1-mediated PTEN ubiquitination [77]. All these data reinforce our results about the promising use of miR-93-5p as PC biomarkers.…”
Section: Discussionsupporting
confidence: 81%
“…There are also some reports in PC. Furthermore, the role of IGF2 messenger RNA binding protein 3 (IMP3) produces an acceleration in PC progression through activating PI3K/AKT/mTOR signaling pathway via increasing SMURF1-mediated PTEN ubiquitination [77]. All these data reinforce our results about the promising use of miR-93-5p as PC biomarkers.…”
Section: Discussionsupporting
confidence: 81%
“…Comprised of a catalytic C-terminal HECT domain and N-terminal C2 domain and WW domains responsible for cellular localization and substrate recognition IRS-2 [249]; AR [250]; ErbB3 levels and signaling [251] IGF signaling and mitogenic activity [249]; cancer cell proliferation in vitro and in vivo; sensitization of cancer cells for growth inhibition by an anti-ErbB3 antibody [251] SMURF1 SMAD specific E3 ubiquitin protein ligase 1 PTEN [252] PCa progression [252]; invasion [253] WWP1 WW domain-containing E3 ubiquitin protein ligase-1 TGFβ [254]; p63 [255]; KLF5 [256] Migration and invasion [257]; 22Rv1 cells colony formation; PC-3 cells proliferation and TGFβ-mediated growth inhibition [254]; apoptosis [255] WWP2…”
Section: E6apmentioning
confidence: 99%
“…Phosphatase and tensin homolog (PTEN) is a very commonly mutated tumor suppressor gene in human cancers, including HCC. 26 , 27 , 28 , 29 Accumulating evidence has shed light on PTEN activity, which can be regulated by mutations, epigenetic silencing, abnormal protein, transcriptional inhibition, localization, and posttranslational modification. 30 , 31 , 32 At the same time, some data have indicated that decreased PTEN expression is a common event in HCC and is associated with disease stage, tumor grade and size, and increased expression of tumor markers.…”
Section: Introductionmentioning
confidence: 99%